A Meier-Gorlin syndrome mutation in a conserved C-terminal helix of Orc6 impedes origin recognition complex formation. - Bleichert, F.; Balasov, M.; Chesnokov, I.; Nogales, E.; Botchan, M.R.; Berger, J.M. (eLife, 2013)
In eukaryotes, DNA replication requires the origin recognition complex (ORC), a six-subunit assembly that promotes replisome formation on chromosomal origins. Despite extant homology between certain subunits, the degree of structural and organizational overlap between budding yeast and metazoan ORC has been unclear. Using 3D electron microscopy, we determined the subunit organization of metazoan ORC, revealing that it adopts a global architecture very similar to the budding yeast complex. Bioinformatic analysis extends this conservation to Orc6, a subunit of somewhat enigmatic function. Unexpectedly, a mutation in the Orc6 C-terminus linked to Meier-Gorlin syndrome, a dwarfism disorder, impedes proper recruitment of Orc6 into ORC; biochemical studies reveal that this region of Orc6 associates with a previously uncharacterized domain of Orc3 and is required for ORC function and MCM2-7 loading in vivo. Together, our results suggest that Meier-Gorlin syndrome mutations in Orc6 impair the formation of ORC hexamers, interfering with appropriate ORC functions.